Implementasi Algoritme SIMON untuk Enkripsi dan Dekripsi Berbasis QR Code - Ngr. Putu Raka Novandra Asta; Ari Kusyanti; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Some advantages of e-payment model is the form of use of use of time, energy, and efficient. Positive and significant effects have been inflicted on this payment against the trade of goods and services. On the other hand it has been found in the field that there is data tapping by hackers disguised as customers to hack customer data. To prevent data from being hacked required a method to ensure data is kept secure. Cryptography and QR Code are methods for data to be secure. The research objective is to implement the SIMON algorithm 32 & 64 for a simple QR Code payment in the form of mobile application software. This research results that the implementation of SIMON 32 & 64 algorithm for QR Code payment can function to secure data. The results of other studies show that the validation of the plaintext and ciphertext based on the SIMON test vector shows that the results are the same as the SIMON test vector. Through encryption processing and decryption shows the total key expansion time is 5.3 seconds. The Total encryption time is 4.7 seconds. The Total key expansion decryption time is 5.3 seconds. Total Decryption Process is 2.1 seconds.